Dukha Mobility in a Constructed Environment: Past Camp Use Predicts Future Use in the Mongolian Taiga. Issue 2 (29th April 2019) - Haas, Randall; Surovell, Todd A.; O'Brien, Matthew J.
Abstract : Diverse theoretical perspectives suggest that place plays an important role in human behavior. One recent perspective proposes that habitual and recursive use of places among humans may be an emergent property of obligate tool use by our species. In this view, the costs of tool use are reduced by preferential occupation of previously occupied places where cultural materials have been discarded. Here we use the model to generate five predictions for ethnographic mobility patterns. We then test the predictions against observations made during one month of coresidence with a residentially mobile Dukha family in the Mongolian Taiga. We show that (1) there is a strong tendency to occupy previously used camps, (2) previously deposited materials are habitually recycled, (3) reoccupation of places transcends kinship, (4) occupational hiatuses can span decades or longer, and (5) the distribution of occupation intensity among camps is highly skewed such that most camps are not intensively reoccupied whereas a few camps experience extremely high reoccupation intensity. These findings complement previous archaeological findings and support the conclusion that the constructed dimensions of human habitats exert a strong influence on mobility patterns in mobile societies. Abstract : Perspectivas teóricas diversas sugieren que el lugar cumplió un rol importante en el comportamiento humano. Una perspectiva reciente propone que el uso habitual y recurrente de lugares es una propiedad emergente del uso obligatorio de herramientas por nuestro especie. En esta visión, los costos de uso de herramientas son reducidos por una ocupación preferencial de lugares ocupados previamente, donde materiales culturales fueron depositados. Aqui usamos este modelo para hacer cinco prediciones para los patrones de movilidad de cazadores-recolectores. Despues probamos las prediciones en contra de observaciones de los movimientos residenciales de una familia Dukha en la Taiga de Mongolia. Mostramos que (I) hay una tendencia fuerte para ocupar los campamentos tomados previamente, (II) materiales depositados son reciclados habitualmente, (III) las re-ocupaciones de los lugares van más allá del parentesco, (IV) las interrupciones en ocupaciones podría abarcar décadas o más y (V) la distribución de la intensidad de ocupación de campamentos es muy sesgado, tal que la mayoría de los campamentos no se vuelven a ocupar intensivamente, mientras que muy pocos campamentos muestran una alta reocupación intensiva. Estos hallazgos se complementan con descubrimientos arqueologicos previos y apoyan la conclusión que las dimensiones construidas del hábitat humano ejercen un gran influencia en los patrones de movilidad en sociedades móviles.